The role of cVA and the Odorant binding protein Lush in social and sexual behavior in Drosophila melanogaster - Billeter, Jean-Christophe; Levine, Joel (Frontiers in Ecology and Evolution, 2015)
Social living is beneficial because it allows conspecifics to interact in ways that increase their chances of survival and reproduction. A key mechanism underlying these benefits is the ability to recognize conspecifics; thus, allowing the production of coordinated social interactions. Identification of such individuals is often through chemical communication: the individuals' pheromonal profile indicates their sex, species, and even past experiences. However, we know little about how the chemosensory system of conspecifics detects and how the nervous system processes this information. One of the best documented pheromonal detection mechanisms is that of cis-Vaccenyl Acetate (cVA) made by male Drosophila melanogaster and transferred to females during mating. Sensing of cVA by males inhibits courtship behavior toward already mated females. Sensing of cVA on other males also inhibits courtship and increases aggression. In this hybrid review/research article, we discuss the pheromonal system of Drosophila putting an emphasis on the molecular and cellular mechanisms involved in cVA sensing by the olfactory system, perception by the nervous system and ultimately the regulation of social interactions. The behavioral effect of cVA is context- as well as experience-dependent leading us to conclude that cVA plays a modulatory role in regulating social interactions rather than being a recognition pheromone. We also provide new behavioral data on the function of the Odorant Binding Protein Lush, which binds cVA in olfactory sensilla and help sensing this chemical. Our data indicate that lush may be involved in the sensing of additional pheromones to cVA and suggest the existence of a lush-independent cVA detection system. Interpretation of our data in the light of our current knowledge about pheromonal recognition in Drosophila indicates that this system is incompletely understood.